A Thematic Study of Journalistic Principles in the Light of Qur’anic Verses - Hafiz Muhammad Hassan Malick (`, 2025)
This research explores the foundational ethics of journalism derived from Qur’anic guidance, presenting a thematic analysis rooted in Islamic epistemology. Moving beyond conventional Western media frameworks, the study examines how the Qur’an lays a comprehensive moral and professional framework for communication, truth dissemination, and societal responsibility. Beginning with the concept of truthfulness (ṣidq) and transparency, the research investigates the Qur’anic command to uphold honesty in public discourse. It then examines the principle of verification (tathabbut) as mandated in Surah al-Ḥujurāt (49:6), establishing the necessity of investigative integrity in news transmission. Other core values, such as justice (ʿadl), non-defamation, trustworthiness (amānah), and respectful speech, are evaluated as essential pillars of an Islamic journalistic ethic. The paper further highlights the Qur'anic objective of preserving communal harmony and preventing discord, emphasizing the role of media in upholding unity (ukhuwwah) and fulfilling the duty of enjoining good and forbidding evil (amr bil-maʿrūf wa nahy ʿan al-munkar). By referencing classical exegesis—including Tafsīr al-Kashshāf, al-Rāzī, Ibn Kathīr, al-Qurṭubī, and al-Ālūsī—this study draws direct connections between revelatory guidance and modern journalistic practices. It critically evaluates the ethical vacuum in contemporary media and proposes Qur’an-based reforms to align journalistic functions with truth, accountability, and reformative intent. The research concludes that the Qur’anic paradigm offers not only a moral compass for journalists but a strategic model for reorienting the media toward collective well-being, justice, and social rectitude. Keywords: Qur’an and Journalism, Islamic Media Ethics, Justice in Journalism